The Myriad Legacies of 1917
XVII, 299 p. 20 illus., 14 illus. in color.
Keywords: This book explores the ramifications of 1917, arguing that it was a cataclysmic year in world history. In this volume, thirteen scholars reflect on the myriad legacies of the year 1917 as a year of war, revolution, upheaval and change. Crisscrossing the globe and drawing on a range of disciplinary approaches, from military, social and economic history to museum, memory and cultural studies, the collection highlights how the First World War remains ‘living history’. With contributions on the Russian revolutions, the entry of the United States into the war, the Caucasus and Flanders war fronts, as well as on India and New Zealand, and chapters by pre-eminent First World War academics, including Jay Winter, Annette Becker, and Michael Neiberg, the collection engages all with an interest in the era and in the history and commemoration of war.